2013
DOI: 10.1179/1476830513y.0000000052
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil phenols and neuroprotection

Abstract: Olive oil is a rich source of phenolic components which have a wide variety of beneficial health effects in vitro, in vivo, and clinically. The beneficial effects of olive oil phenols attributed to a variety of biological activities including free radical scavenging/antioxidant actions, anti-inflammatory effects, anti-carcinogenic properties, and anti-microbial activities. On the other hand, olive oil phenols have been shown to be some of neuroprotective effects against cerebral ischemia, spinal cord injury, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 82 publications
0
54
0
1
Order By: Relevance
“…Phenols found in olive oil have a wide range of beneficial effects because of their anti-inflammatory effect and free radical scavenger mediating a neuroprotective effect demonstrated in animal models of hypoxic injury, Parkinson's disease, and MS [33]. Although many components of the MeDi are felt to be beneficial, research suggests that following the diet as a whole is better than individual components [34]. Several studies have highlighted the benefits of the MeDi including reduction in all-cause mortality, ischemic heart disease, hypertension, diabetes, obesity, dementia, and several types of cancers [33].…”
Section: Mediterranean Dietmentioning
confidence: 97%
See 1 more Smart Citation
“…Phenols found in olive oil have a wide range of beneficial effects because of their anti-inflammatory effect and free radical scavenger mediating a neuroprotective effect demonstrated in animal models of hypoxic injury, Parkinson's disease, and MS [33]. Although many components of the MeDi are felt to be beneficial, research suggests that following the diet as a whole is better than individual components [34]. Several studies have highlighted the benefits of the MeDi including reduction in all-cause mortality, ischemic heart disease, hypertension, diabetes, obesity, dementia, and several types of cancers [33].…”
Section: Mediterranean Dietmentioning
confidence: 97%
“…The diet consists of high intake of fruit, vegetables, monounsaturated fat, fish, whole grains, legumes, and nuts; moderate alcohol consumption; and a low intake of red meat, saturated fat, and refined grains. Olive oil is the main source of fat in the MeDi [34]. Phenols found in olive oil have a wide range of beneficial effects because of their anti-inflammatory effect and free radical scavenger mediating a neuroprotective effect demonstrated in animal models of hypoxic injury, Parkinson's disease, and MS [33].…”
Section: Mediterranean Dietmentioning
confidence: 99%
“…Olea europaea L. is one of the most diffuse plants in the Mediterranean area, from which the extra‐virgin olive oil (EVOO) is traditionally obtained by cold pressing of olive fruits. EVOO represents the most used dressing in the Mediterranean diet, and many studies report its beneficial effects on human health (Battino et al, ; Buckland & Gonzalez, ; Covas, Torre, & Fitó, ; Delgado‐Lista et al, ; Estruch et al, ; Finicelli et al, ; Guasch‐Ferré et al, ; Khalatbary, ; Konstantinidou et al, ; Pérez‐Martínez, García‐Ríos, Delgado‐Lista, Pérez‐Jiménez, & López‐Miranda, ). This last aspect has received increased interest by the consumers of functional foods (containing biologically active minor components; Bonechi et al, ; Bonechi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Olive extracts are a natural source of polyphenols, widely considered to be potentially beneficial for health. Many studies have revealed their capacity to scavenge reactive species, and human intervention studies have shown that olive polyphenols decrease the levels of oxidized low‐density lipoproteins in plasma and positively affect several biomarkers of oxidative damage . A more recent study assessed the antioxidant activity of both individual and combined phenolics in Olea europaea L .…”
Section: Introductionmentioning
confidence: 99%